2014
DOI: 10.5510/ogp20140100185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inorganic salt on the structure of filter cake of water based drilling fluid

Abstract: ELMİ ƏSƏRLƏR • PROCEEDINGS • НАУЧНЫЕ ТРУДЫ 30 №1Filter cake formed by large particles has an increased porosity, and also, a greater permeability. The objective of this work is to provide a comprehensive review of the microscopic structure and elementary composition, particle size distribution, and polymer concentration in different layers of the filter cake to reveal the mechanism which led to the changes of structure of filter cake. The effect of inorganic salt on the structure of filter cake has been conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To control filtrate loss to the formation, specific additives are generally used that increase the fluid's viscosity so that filter cake is formed inside and outside the borehole . If these additives are not selected properly, they can cause a significant reduction of the permeability and damages to the formation …”
Section: Introductionmentioning
confidence: 99%
“…To control filtrate loss to the formation, specific additives are generally used that increase the fluid's viscosity so that filter cake is formed inside and outside the borehole . If these additives are not selected properly, they can cause a significant reduction of the permeability and damages to the formation …”
Section: Introductionmentioning
confidence: 99%
“…For example, Elkatatny et al [10,21] found the filter cake was composed of two layers, and the microstructure, thickness and porosity of the cake layer were characterized by using SEM and CT scan. Y.Rugang et al [22,23] claimed that drilling fluid components have a non-negligible effect on filter cake characteristics, and presented the effect of inorganic salt on the structure of filter cake of water based drilling fluid.…”
Section: Introductionmentioning
confidence: 99%